Analysis of the Implementation of the Hospital Information System (SIMRS) in the Inpatient Ward of Harapan Bunda Hospital in Lampung Using the Technology Acceptance Model (TAM) Approach - Ari Hidayat; Miftahul Rizki; Setia Wulandari (Green Publisher Indonesia, 2026)
The implementation of the Hospital Information System (SIMRS) in inpatient wards is crucial for improving service quality, efficiency, and data accuracy in hospitals. However, its success largely depends on user acceptance among healthcare workers. The purpose of this study is to analyze the implementation of the Hospital Information System (SIMRS) in the inpatient ward of Harapan Bunda Hospital, Lampung, using the Technology Acceptance Model (TAM) approach. The respondents of this study were 138 inpatient nurses and nursing professionals who use the hospital information system in inpatient wards. The data were analyzed using the PLS-SEM (Partial Least Squares Structural Equation Modeling) method. The results show that the Perceived Usefulness variable has a positive and significant effect on Attitude toward Using and Behavioral Intention to Use. Perceived Ease of Use has a positive and significant effect on Attitude toward Using and exerts a very strong influence on Perceived Usefulness. Furthermore, Attitude toward Using has a positive and significant effect on Behavioral Intention to Use. However, Behavioral Intention to Use has not been shown to have a significant influence on Actual Usage. External factors outside the TAM model are strongly suspected to influence the implementation of actual system use in the field.